First description of a hybrid tumor of the sublingual gland - Eichhorn, Wolfgang; Precht, Clarissa; Wehrmann, Manfred; Hickmann, Elisabeth; Eichhorn, Marc; Zeuch, Jürgen; Löning, Thomas; Friedrich, Reinhard E.; Heiland, Max; Hoffmann, Jürgen (Anticancer research, 2013)
Background: Hybrid tumours of the salivary glands are rare neoplasms. They are composed of at least two different tumour entities located in the same topographic area and account for only 0.1% of all salivary gland tumours. The most common component is an adenoid cystic carcinoma. There are several possible forms of hybrid tumours, which are most commonly located in the parotid gland. Case Report: We report on a 59-year-old female, who presented with a lesion of the caruncula of the left sublingual gland. The biopsy showed an adenoid cystic carcinoma in combination with a salivary duct carcinoma. Treatment consisted of tumour resection, bilateral selective neck dissection and adjuvant radiotherapy. Histopathologically, at least 30% of the tumour mass was composed of a salivary duct carcinoma and 70% of an adenoid cystic carcinoma. At 58 months after treatment, the patient is alive without evidence of recurrent disease. Conclusion: To our knowledge, the presented case is the first description of a hybrid tumour of the sublingual gland. Furthermore, the post-therapeutic course is encouraging, as hybrid tumours of the salivary glands usually have a poor prognosis.
Gesehen am 08.01.2021